Shari’ah Heterogeneity of Indian Islamic Waqf Law (IIWL) and Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) Standard: A Comparative Study in Light of Classical Rulings - Jawwad Ali; Yousuf Azim Siddiqi; Nor Asiah Mohamad; Rusni Hassan (Journal of Islamic Finance, 2023)
The establishment of the institution of Waqf, or Islamic endowment, was evident from the early days of Islam. Hence, the Prophet’s companions ( صلى الله عليه وسلم) had established Waqf for their family members or needy people. Over some time, Waqf played a vital role in Islamic history by serving sectors like health, education, and social welfare. With the introduction of Islam in India, the institution of Waqf spread in Delhi and then to other parts. Governance of these Waqf bodies was directly managed by the royal court of the Muslim emperor. After the fall of the Mughal Empire, some acts were enacted by the British empire. Post-independence of India, new laws and acts related to Waqf were enacted, but Shari’ah observation was not the core theme of these acts. In 1972, the All-India Muslim Personal Law Board (AIMPLB) was formed, and it planned to codify fiqh rulings related to family matters and Waqf. This study compares the rulings of Indian Islamic Waqf Law (IIWL) with AAOIFI’s Shari’ah Standard on Waqf (AAOIFI refers to: no 60, issued in 2019). To achieve this objective, the qualitative method is adopted. The study is divided into a) Introduction, b) Literature Review, c) Analysis, and d) Conclusion and Recommendation. The study highlighted 67 rulings of AAOIFI and IIWL and found five instances of Shari’ah heterogeneity where IIWL has less favourable implications, besides 22 rulings where IIWL has no stand. The study recommends revising IIWL to ensure the growth of Waqf and longer sustainability.